1994
DOI: 10.1002/cyto.990150414
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of ceroid accumulation in macrophages by flow cytometry

Abstract: The accumulation in macrophages of ceroid, an sutofluorescent polymer composed of oxidised protein and lipid, can be monitored seiniquantitatively by staining techniques. However, such methods are crude and give little infor mation about the amount of ceroid within cells. Flow cytometry, however, can give a quantitative assessment of cellular ceroid accumulation in vitro. Recently, flow cytometry was explored as a method for measurement of the accumulation in macrophages of ceroid. The accumulation appeared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Also, 2 lipopigments, ceroid and carotenoids, were related to atherosclerotic lesion fluorescence emission. 15,31,32 Ceroid, an end product of lipoprotein oxidation, is found in macrophages and in lesions with lipid-rich necrotic cores. Carotenoids are present in lipid-rich lesion cores.…”
Section: Fluorescence Of Coronary Artery: Interpretation In Terms Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, 2 lipopigments, ceroid and carotenoids, were related to atherosclerotic lesion fluorescence emission. 15,31,32 Ceroid, an end product of lipoprotein oxidation, is found in macrophages and in lesions with lipid-rich necrotic cores. Carotenoids are present in lipid-rich lesion cores.…”
Section: Fluorescence Of Coronary Artery: Interpretation In Terms Of mentioning
confidence: 99%
“…The main fluorescent components of normal and diseased arterial wall, together with their emission characteristics, are depicted in Table II (http://atvb.ahajournals.org). [25][26][27][28][29][30][31][32] The fluorescence of the structural proteins elastin and collagen was related primarily to artery fluorescence. Previous research 8,25 demonstrated that the fluorescence of elastic fibers within the internal lamina or media predominates over the emission of normal coronary artery or aorta, respectively, whereas the fluorescence of collagen (30% to 60% dry weight 3 ) prevails over the emission of advanced collagenous lesions (type V a or fibrous plaques).…”
Section: Fluorescence Of Coronary Artery: Interpretation In Terms Of mentioning
confidence: 99%